Influence of pressures up to 50 bar on two-stage anaerobic digestion. (May 2017) - Merkle, Wolfgang; Baer, Katharina; Lindner, Jonas; Zielonka, Simon; Ortloff, Felix; Graf, Frank; Kolb, Thomas; Jungbluth, Thomas; Lemmer, Andreas
Highlights: The influence of pressure on anaerobic digestion up to 50 bar was examined experimentally. Increasing pressure decreases pH value in the methane reactor until 6.53. Increasing pressure increases methane content over 90%. Increasing pressure decreases specific methane yield until 0.26 L g –1 CODadded . The pressurized methane reactor operates very stable. Abstract: The concept of pressurized two-stage anaerobic digestion integrates biogas production, purification and pressure boosting within one process. The produced methane-rich biogas can be fed into gas grids with considerably less purification effort. To investigate biogas production under high pressures up to 50 bar, a lab scale two-stage anaerobic digestion system was constructed including one continuously operated pressurized methane reactor. This investigation examined the effects of different operating pressures in methane reactor (10, 25, 50 bar) on biogas quantity and quality, pH value and process stability. By increasing operating pressures in methane reactor, the pH value decreased from 6.65 at 10 bar to 6.55 at 50 bar. Simultaneously, methane content increased from 79.08% at 10 bar to 90.45% at 50 bar. The results show that methane reactors can be operated up to 50 bar pressure continuously representing a viable alternative to commonly used gas upgrading methods because of reduced purification effort.